Effect of Temperature and Mole Ratio on the Synthesis Yield of Rhenium-Tetrofosmin - W Widyastuti; A.H. Gunawan (PPIKSN-BATAN, 2015)
Technetium-99m (99mTc) tetrofosmin is widely used in nuclear medicine as a diagnostic agent for myocardial perfusion and as a tumor imaging agent. As a parenteral preparation it requires an evaluation of its pharmacokinetics and stability in-vivo. Since 99mTc has a short half-life and is only available in very low concentrations, it is impossible to characterize its chemical properties and presence in the body. Due to this reason, only technetium-99 (T1/2 = 5 × 105 years), which is available in macro quantities, or natural rhenium can be used for this purpose. In this study rhenium-188 (188Re) tetrofosmin will be synthesized and applied, because non-radioactive Re can be easily obtained. Synthesis and radiochemical purity analysis of carrier-added 188Re-tetrofosmin were carried out as a model to study the in-vivo stability of technetium-99m tetrofosmin. Rhenium-188 was used as a tracer to identify the formation of rhenium tetrofosmin. Rhenium gluconate was synthesized first prior to the formation of rhenium tetrofosmin. The quality of labeling for both rhenium gluconate and rhenium tetrofosmin was analyzed using paper- and thin-layer chromatography, respectively. Rhenium gluconate can be synthesized with high labeling yield within 1 hour, whereas rhenium tetrofosmin was synthesized both in room temperature and in an elevated temperature with various tetrofosmin-to-rhenium mole ratios.The results showed that heating at 95oC led to a higher yield of more than 90% within 30 minutes. Rhenium tetrofosmin could be produced in high radiochemical purity using an excess of tetrofosmin with mole ratio of 2000. It is concluded that rhenium tetrofosmin could be synthesized through the formation of rhenium gluconate, and a higher yield could be obtained in a shorter time by heating process. Received: 04 October 2014; Revised:14 April 2015; Accepted:15 April 2015